Dopamine multivalent-modified polyaspartic acid for MRI-guided near-infrared photothermal therapy. (14th March 2023) - Du, Liang; Chen, Wei; Zhong, Jie; Yan, Shuang; Yang, Chenwu; Pu, Yu; Zhu, Jiang; Chen, Tianwu; Zhang, Xiaoming; Wu, Changqiang
Abstract: Nanophotothermal agents that provide efficient and precise treatment at tumor sites are attracting increasing attention in biomedicine. In particular, the method combination of nanophotothermal agents and magnetic resonance imaging (MRI) shows great promise for biomedical therapeutic applications. Herein, a simple nanophotothermal agent with dopamine multivalent-modified polyaspartic acid chelated superparamagnetic iron oxide (SPIO) and ferric ion (SPIO@PAsp-DAFe/PEG) was developed for MRI-guided near-infrared photothermal therapy (PTT). SPIO@PAsp-DAFe/PEG was random SPIO nanocluster with good water solubility, had a diameter of 57.8 ± 7.8 nm in dynamic light scattering, negatively charged surface (zeta potential = −11 mV), exhibited good stability and outstanding photothermal conversion efficiency (35.4%) and produced superior magnetic resonance enhanced imaging. In the experiment with tumor-bearing mice, the MRI not only monitored the accumulation of SPIO@PAsp-DAFe/PEG nanocomposites enhanced by near-infrared irradiation after intravenous administration but also determined the appropriate time window for PTT. With the use of MRI-guided near-infrared therapy, the SPIO@PAsp-DAFe/PEG nanocomposites provided excellent therapeutic effects, confirming their great potential as effective MRI/PTT therapeutic agents. Graphical Abstract: